Fanum and philosophy: Cicero and the death of Tullia - Englert, Walter (Ciceroniana On Line, 2017)
After the death of Tullia, Cicero wrote repeatedly in his letters to Atticus that he intended to build a shrine (fanum) to divinize his daughter, but he never carried out his plans. I argue that by comparing Cicero’s comments in the Letters to Atticus to passages in the Consolatio and Tusculan Disputations we learn why Cicero did not build the fanum. After announcing a monument for Tullia in the Consolatio and discussing it in his letters, in the Tusculan Disputations Cicero shows that he changed his mind about the fanum. Endorsing Stoic arguments about the nature of grief, he argued that building a monument to the dead, as Artemisia had done with the famous Mausoleum, would be counterproductive and prolong grief needlessly. The article ends by showing how passages about losing a loved one in the De Senectute and De Amicitia are consistent with Cicero’s view in the Tusculan Disputations. Dopo la morte di Tullia, Cicerone, nelle lettere ad Attico, mostra ripetutamente l’intenzione di far costruire un tempio (fanum) per divinizzare sua figlia; tuttavia, non riesce a portare a compimento il suo proposito. Grazie al raffronto tra i commenti, desumibili dalle Lettere, e alcuni passi tratti dalla Consolatio e dalle Tusculanae Disputationes, è possibile comprendere perché il fanum non sia stato costruito. Dopo aver dichiarato, nella Consolatio, di dedicare un monumento a Tullia e dopo averne discusso, nelle Lettere, Cicerone cambia la sua opinione nelle Tusculanae Disputationes. Conformandosi alle tesi di matrice stoica, relative alla natura del dolore, egli ritiene che costruire un monumento in onore di un morto – come fece Artemisia con il famoso Mausoleo – sarebbe stato non solo controproducente, ma avrebbe anche prolungato inutilmente il dolore. In conclusione, l’articolo mostra come i passi relativi alla perdita di una persona amata nel De Senectute e nel De Amicitia siano coerenti con la tesi espressa nelle Tusculanae Disputationes.